Management of Bilateral Postpartum Uterine Prolapse In a Persian Cat At Klinik Hewan Jogja - Marbun, Indah Frysay Eklesia; S.W., Titis; Pratiwi, Herlina (Jurnal Sain Veteriner, 2026)
Uterine prolapse is uterine mucosa eversion or protrusion through the cervix or vagina. Rarely do dogs or cats have uterine prolapse. occurs within 48 hours of delivery. Dystocia or regular labor might cause uterine prolapse. According to the cat owner, she gave birth at home to six healthy cats. After parturition, the cat was transferred to Klinik Hewan Jogja at 22.00 WIB with eversion of both uterine cornua, hemorrhage, hemorrhagic shock, and edema. It was determined that the cat had uterine prolapse in both cornuas. Ovariohysterectomy is surgical. Preoperative preparation includes tools, materials, the patient, the operator, and the assistant operator. Amputating both uterine cornua occurs intraoperatively. After surgery, give the cat ceftriaxone 20 mg/kg BW q12h IM, tramadol 3 mg/kg BW q12h SC, tranexamic acid 20 mg/kg BW q12h IM/IV, and iron supplement 0.4 ml q24h IM for 3 days. Q24h wound care includes cleaning with cotton wool moistened with NaCl+PenStrep and applying enough topical chloramphenicol cream. Based on anamnesis, physical examination, and clinical observations, the cat was diagnosed with uterine prolapse and treated with an ovariohysterectomy. After three days of observation, it was declared cured with no suture wound problems.